2013
DOI: 10.1111/imj.12230
|View full text |Cite
|
Sign up to set email alerts
|

Developing a national database for metastatic colorectal cancer management: perspectives and challenges

Abstract: Multistate, project-specific data collection involving large numbers of patients is achievable. Providing invaluable insight into the routine clinical management of metastatic colorectal cancer in the era of targeted therapies, this also creates a significant resource for research, including many questions not being addressed by clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…Data obtained from the Treatment of Recurrent and Advanced Colorectal Cancer (TRACC) registry was used for this analysis . Data are collected at point of care, and include the Charlson comorbidity index and the Eastern Cooperative Oncology Group (ECOG) performance status, both of which are mandatory data fields for every patient enrolled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data obtained from the Treatment of Recurrent and Advanced Colorectal Cancer (TRACC) registry was used for this analysis . Data are collected at point of care, and include the Charlson comorbidity index and the Eastern Cooperative Oncology Group (ECOG) performance status, both of which are mandatory data fields for every patient enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…Data obtained from the Treatment of Recurrent and Advanced Colorectal Cancer (TRACC) registry was used for this analysis. 7 Data are collected at point of care, and include the Charlson comorbidity index 8 and the Eastern Cooperative Oncology Group (ECOG) performance status, both of which are mandatory data fields for every patient enrolled. All patients with mCRC (American Joint Committee on Cancer guidelines Stage IV) 9 diagnosed at participating hospitals from July 2009, when the registry was initiated, through to February 2014 were included in this analysis.…”
Section: Methods Datasetmentioning
confidence: 99%
“…[51,52] However, the therapeutic effect of bevacizumab for peritoneal disease in mCRC has been poorly described. The AGITG MAX trial, [53] the only randomized Phase III trial where the outcomes of mCRC patients with peritoneal metastasis receiving bevacizumab treatment were presented, together with 2 registry-based studies—TRACC [54] and NSWCC, [55] have showed that the addition of bevacizumab to first-line chemotherapy was associated with prolonged PFS within the peritoneal subgroup. But the OS benefits were not consistently seen across studies.…”
Section: Discussionmentioning
confidence: 99%
“…TRACC is a prospective, multicentre registry collating patient and disease characteristics, treatment strategies and outcomes for mCRC patients. Established in 2009, it is a collaboration between Biogrid Australia and public and private cancer centres in both metropolitan and regional Australia . Data are stored at individual sites as property of the participating site; Biogrid integrates de‐identified data from sites for access of individual researchers after application, and facilitates database upkeep.…”
Section: Methodsmentioning
confidence: 99%